Differential association of STAT3 and HK‐II expression in hepatitis B virus‐ and hepatitis C virus‐related hepatocellular carcinoma. Issue 9 (8th March 2016) - Li, Man; Wang, Weihua; Jin, Rui; Zhang, Tieying; Li, Na; Han, Qunying; Wei, Ping; Liu, Zhengwen
Abstract : STAT3 and hexokinase II (HK‐II) are involved in viral infection and carcinogenesis of various cancers including hepatocellular carcinoma (HCC). The roles of STAT3 and HK‐II in hepatitis B virus (HBV)‐ and hepatitis C virus (HCV)‐related HCC remain largely unclear. This study examined STAT3 and HK‐II expression in HBV‐ and HCV‐related HCC, HBV‐related liver fibrosis, and normal control liver by using tissue microarray and immunohistochemical method. Results showed that STAT3 expression in HBV‐related HCC, HCV‐related HCC, and HBV‐related liver fibrosis was significantly higher than in control liver ( P < 0.001, P = 0.016, and P = 0.005, respectively) and had no significant differences between these three diseased liver tissues. The HK‐II expression in HBV‐related HCC was significantly higher than that in HCV‐related HCC, HBV‐related liver fibrosis, and control liver ( P = 0.007, P = 0.029, and P = 0.008, respectively) but had no significant elevation in and no significant differences between HCV‐related HCC, HBV‐related liver fibrosis, and control liver. The HK‐II expression was significantly correlated to STAT3 expression in HBV‐related HCC ( P = 0.022), but no correlation was observed in HCV‐related HCC, HBV‐related liver fibrosis, and control liver. In conclusion, STAT3 expression is upregulated in both HBV‐ and HCV‐related HCC, while HK‐II is predominantly upregulated and correlated to STAT3 in HBV‐related HCC. These differential expression and association may suggest the distinct roles of STAT3 and HK‐II in hepatocarcinogenesis of HBV and HCV infection. Studies are needed to confirm the relationship of STAT3 and HK‐II and to examine the underlying mechanisms. J. Med. Virol. 88:1552–1559, 2016 . © 2016 Wiley Periodicals, Inc.